Trends in cochlear implant candidacy in children. Issue 10 (October 2017) - Maggs, Justine; Ambler, Marette; Hanvey, Kate
Abstract: In the last 30 years, the field of cochlear implantation has rapidly evolved. Technological advances in hardware and corresponding developments in surgical techniques, along with new sound processing strategies and innovative rehabilitation, have combined to maximise functional outcomes. Informed by the evidence base of such outcomes, the inclusion criteria for children who might benefit from a cochlear implant (CI) has been refined and expanded. CIs are now the standard of care for children with severe to profound hearing loss where the desired outcome is spoken language. There are several emerging trends within the field of paediatric CIs that have already translated into clinical practice in some countries, but have not yet been universally adopted. These include, but are not limited to, the expansion of audiometric CI candidacy criteria for cohorts with: (1) more residual hearing; (2) partial hearing which may benefit from electric-acoustic stimulation (EAS); and (3) asymmetric hearing levels. This review will describe the historical context and provide an overview of the candidacy trends as they relate to children.